Niketas Stethatos der „Beherzte“? - Hinterberger, Martin (Byzantinische Zeitschrift, 2010)
According to a well-established opinion, the theological writer Niketas Stethatos († ca 1090) had received his surname “the Brave” due to his courageous criticism of the amorous adventures of Constantine IX. In fact, Stethatos is a family name and means “with a broad chest”.